Basic Urdu - Ranjan, Rajiv (Open textbook library., 2022)
Basic Urdu is a theme-based, interactive open-source online textbook for the true novice learners of the Urdu language. The book uses mixed pedagogical approaches to language teaching to match diverse teaching and learning styles. It aims to help learners achieve intermediate low to mid-proficiency levels set by the American Council on the Teaching of Foreign Languages (ACTFL).